THE INFLUENCE OF EXTRINSIC MOTIVATIONAND WORK ENVIRONMENTON PERFORMANCE OF EMPLOYEES IN PT. ALAS PETALA MAKMUR - Agus Frianto (USIM, THAMKAM, KHON KAEN, UMY, 2016)
The company progress cannot be separated from the presence and human resources has an important role in achieving efficiency and effectiveness the organization can be managing physical resources, financial, and human beings in the most effective and efficient. Extrinsic Motivation and Work Environment is one of the factors that can affect the performance of the employees. The purpose of the study is to determine the influence of extrinsicmotivationand work environment on performance of employees in PT. Alas Petala Makmur and determine the condition of each variable. Sample that being taken171respondents with the method samples universe. Instrument of analysis use iin the research is including the validity, realibility, and multiple linear regresion analysis with the help SPSS17.Based oncausality testfounda significantpositiveeffectof extrinsic motivationand the work environmenton employee performanceThe results showedthat the magnitude ofthe effectof extrinsic motivationand the work environmenton employee performancehave strong influence on employee’s performance in PT. Alas Petala Makmur either partial or simultan Keywords:The company progress cannot be separated from the presence and human resources has an important role in achieving efficiency and effectiveness the organization can be managing physical resources, financial, and human beings in the most effective and efficient. Extrinsic Motivation and Work Environment is one of the factors that can affect the performance of the employees. The purpose of the study is to determine the influence of extrinsicmotivationand work environment on performance of employees in PT. Alas Petala Makmur and determine the condition of each variable. Sample that being taken171respondents with the method samples universe. Instrument of analysis use iin the research is including the validity, realibility, and multiple linear regresion analysis with the help SPSS17.Based oncausality testfounda significantpositiveeffectof extrinsic motivationand the work environmenton employee performanceThe results showedthat the magnitude ofthe effectof extrinsic motivationand the work environmenton employee performancehave strong influence on employee’s performance in PT. Alas Petala Makmur either partial or simultan Keywords: ExtrinsicMotivation, Work Environment, Employee Performance